EXPLORATION OF OPPORTUNITIES AND BARRIERS TO CITIZENS' DIGITAL PARTICIPATION IN SPATIAL PLANNING IMPLEMENTATION IN BANDUNG CITY - Rachman, Rizky
The phrase "smart city" as a new paradigm in the process of urban development emerged as a result of the rapid development of information and communication technology. Bandung City which has adopted the smart city concept since 2013 has developed various kinds of innovations in the use of technology to support a more communicative governance system in accordance with the principles of smart governance as one of the dimensions in the smart city development concept, including in the domain of spatial planning. One of the innovations carried out by the Bandung City Government is the provision of digital-based participation facilities that aim to increase the intensity of community involvement in the implementation of spatial planning, especially in the implementation of supervision and control of spatial utilization. However, it is indicated that the implementation of digital participation is not running optimally which is believed to be caused by various repressing factors. This study was conducted with the aim of exploring the prospects and barriers to citizens’ digital participation to support the implementation of smart governance principles in supervision and control of spatial utilization in Bandung City. This study uses quantitative approach to conform to the research goal and objectives. There are four research objects, namely variation forms of participation, preferences for choosing communication channels, barriers of participation process, and sociodemographic characteristics of the citizens. Data collection was carried out using a questionnaire survey method to 14 expert respondents and 60 citizen respondents who were selected as research samples. Data analysis was performed by two types of methods. First, descriptive statistical analysis is used for identifying the alternative forms of digital participation in the implementation of supervision and control of spatial utilization, identifying the preferences for choosing digital communication channels as participatory media based on the experts’ and the citizens’ perspective, and identifying the barriers in the implementation of digital participation. Second, inferential statistical analysis with logistic regression method is used to identify the relationship between sociodemographic characteristics with the tendency to choose communication channels as well as a public assessment of barriers in the implementation of digitaliv participation in the context of supervision and control of spatial utilization in Bandung City. The results obtained from this study show that the digital participation has good prospects in supporting the objectives of implementing smart governance principles in supervision and control of spatial utilization in Bandung City. Some alternative forms of participation that can be offered based on the opinion of expert respondents are developing a citizen representation scheme by the professionals in the field of spatial planning as an agent to bridge the delivery of aspirations from the community to the authority, provide a systematic well-designed communication channel in order to generate more interaction between the community and the government in the aim of further spurring discussions that lead to the formation of a common solutions, and also the government must commit to taking into account for every single community aspirations while maintaining its position as the highest authority in every decision-making process. In terms of the use of communication channels, the existing channels are generally considered good in accommodating the needs of the community to be involved in participatory activities.. Instagram, Whatsapp hotline, and the official website provided by Dinas Ciptabintar, as well as LAPOR! and popular social media accounts are the channels that tend to be preferred to be used as a digital-based public participation channel. This study found that barriers to participation from the factor of the community's ability to participate are suspected due to the lack of knowledge about spatial planning as well as the lack of individual ability and experience in conveying advise to the government. In addition, the government's lack of firmness and seriousness in enforcing opportunities for participation in accordance with the mandate of laws and regulations is also considered as a barriers to participation in terms of the government's political will. The results of the analysis also show that there are different of preferences in choosing of communication channels and individual views regarding the barriers experienced by each individual from the respondents and it is found that some of these are influenced by their sociodemographic background. The results of this study can offer a preliminary description of the opportunities for digital participation that can be pursued in order to achieve the level of smart governance in the field of spatial planning in Bandung City. However, this study’s defined population definition makes its findings cannot be generalized to the population of Bandung City as a whole, so the recommendation for conducting broader and in-depth research are given in order to obtain some reliable results that can be used as a reference for strategic plan development for optimizing community participation, especially in the field of spatial planning in the city of Bandungin Bandung City.